ANALISIS EVALUASI PROGRAM PENINGKATAN DAN PENGEMBANGAN PERTANIAN PERKOTAAN KOTA SURAKARTA (Studi Kasus di Kecamatan Banjarsari) - Bekti Wahyu Utami; Kusnandar Kusnandar; Emi Widiyanti (Caraka Tani: Journal of Sustainable Agriculture, 2009)
This research employed a case study strategy in Banjarsari subdistrict, Surakarta Municipality as one of the area representing target program. It was doing with partsipative evaluation, used by of primary and secondary data. This research result indicate the society target program less precise cause by factor of contiguity personal so make result program walk less success. Institution done evaluation just summarize the aid delivery. Other side society also less holding responsible to efficacy and continueing program, cause nothing reward and punishment from this program.